2022
DOI: 10.1016/j.nurpra.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamines for Postacute Sequelae of SARS-CoV-2 Infection

Abstract: Postacute sequelae of SARS-CoV2 (PASC) infection is an emerging global health crisis, variably affecting millions worldwide. PASC has no established treatment. We describe 2 cases of PASC in response to opportune administration of over-the-counter antihistamines, with significant improvement in symptoms and ability to perform activities of daily living. Future studies are warranted to understand the potential role of histamine in the pathogenesis of PASC and explore the clinical benefits of antihistamines in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…It is suggested that immune disturbance from SARS-CoV-2 infection may lead to aberrant mast cell activation and further initiate cascades of inflammatory responses contributing to allergic flare-up [54,55]. Histamine antagonists have been used to relieve long COVID associated symptoms [55,56]. However, the interaction of antihistamines with viral-altered ACE2 pathways remains to be elucidated.…”
Section: Mast Cell Activation Syndrome (Mcas) and Anti-histamine Trea...mentioning
confidence: 99%
“…It is suggested that immune disturbance from SARS-CoV-2 infection may lead to aberrant mast cell activation and further initiate cascades of inflammatory responses contributing to allergic flare-up [54,55]. Histamine antagonists have been used to relieve long COVID associated symptoms [55,56]. However, the interaction of antihistamines with viral-altered ACE2 pathways remains to be elucidated.…”
Section: Mast Cell Activation Syndrome (Mcas) and Anti-histamine Trea...mentioning
confidence: 99%
“…For instance, according to Crook et al [ 52 ], antihistamines are considered potential DR candidates. Significant improvements in long-term symptoms have been reported in case reports [ 53 ] and observational studies [ 54 ]. This seems to be backed by discussions from long-haulers: antihistamines are the most frequently discussed substances and are important (measured by degree centrality) to the cluster of anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the care of PASC patients, it is thus critical that nurses establish a sense of safety with and for patients as the novelty of this condition brings with it uncertainty which can in turn provoke fear and frustration (Lancet, 2021 ). PASC patients report feeling misunderstood, having symptoms dismissed as self‐injury or anxiety and experiencing fear or mistrust of providers as a result (Callard & Perego, 2021 ; Paredes et al, 2021 ; Pinto et al, 2022 ).…”
Section: Conceptual Model Of Trauma‐informed Care For Patients With ...mentioning
confidence: 99%